1993
DOI: 10.1037/0894-4105.7.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Verbal fluency deficits in Parkinson's disease.

Abstract: We administered verbal (category naming, letter fluency) and nonverbal (category drawing, design fluency) tasks to patients with Parkinson's disease (PD). PD patients were significantly impaired only in their category naming for a semantic target like fruit. We tested the hypothesis that compromised lexical retrieval contributed to PD patients' impaired category naming by examining free recall and recognition on a supraspan learning task. PD patients were significantly impaired in free recall but not recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
3
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 43 publications
6
51
3
7
Order By: Relevance
“…However, the research evidence is not consistent with regard to the reported level of impairment. There have been varying reports of performance on verbal fluency, a task commonly employed to estimate abilities related to frontal lobe function, with some studies reporting impaired performance [16,18,20,21], and other studies reporting no difference between PwPD and controls [14,22,23,24]. The verbal fluency task has been variously reported to measure EF, set-shifting, planning, language ability, or global cognition [21,22,25].…”
mentioning
confidence: 99%
“…However, the research evidence is not consistent with regard to the reported level of impairment. There have been varying reports of performance on verbal fluency, a task commonly employed to estimate abilities related to frontal lobe function, with some studies reporting impaired performance [16,18,20,21], and other studies reporting no difference between PwPD and controls [14,22,23,24]. The verbal fluency task has been variously reported to measure EF, set-shifting, planning, language ability, or global cognition [21,22,25].…”
mentioning
confidence: 99%
“…The exact underlying nature of the semantic deficits has yet to be determined. Interestingly, Auriacombe et al (1993) examined the traditional semantic and phonemic fluency tasks, but also examined fluency performance in the non-verbal modality (i.e., design fluency and category drawing task). They found that PD patients' performance on the non-verbal fluency task was comparable to healthy speakers, and confirmed the discrepancy between relatively intact phonemic fluency and impaired semantic fluency.…”
Section: Single Word Production Tasksmentioning
confidence: 99%
“…It is not necessary to retrieve a word form during category drawing, since knowledge of the concept underlying a target superordinate (i.e., vegetable) and the exemplars that contribute to a superordinate is sufficient. To check the hypothesis that PD patients are impaired in the retrieval of semantic information, Auriacombe et al (1993) also administered a supraspan verbal learning task. A large proportion of the PD patients showed difficulties with free recall, but these patients were accurate at recognition, which is consistent with a retrieval deficit, and not an impairment of semantic memory itself.…”
Section: Single Word Production Tasksmentioning
confidence: 99%
“…Patients with Parkinson's disease (PD) frequently show a cognitive deterioration characterized primarily by a dysexecutive syndrome due to the pathological involvement of the frontal and prefrontal cortices and basal ganglia (Verbaan et al, 2007). Different hypotheses have been advanced to account for the semantic impairment found in these patients: a deficiency of semantic representation activation due to storage impairment, a dysfunction in semantic retrieval processes or increased spreading activation in lexical-semantic networks (Raskin et al, 1992;Auriacombe et al, 1993;Watters and Patel, 1999;Foster et al, 2008). A publication investigating cognitive functions in AD and PD patients with dementia (Song et al, 2008) found (with the exception of episodic memory) a similar neuropsychological pattern: both groups of patients showed the same difficulty in the task evaluating semantic knowledge.…”
Section: Introductionmentioning
confidence: 99%